Cultural values and the prevalence of mental disorders in 25 countries: A secondary data analysis. (September 2017) - Heim, Eva; Wegmann, Iris; Maercker, Andreas
Abstract: Rationale: The prevalence of common mental disorders (CMDs, i.e., depression and anxiety) worldwide is substantial, and prevalence rates are higher in high-income than in low- and middle-income countries. This difference might reflect both underlying prevalence rates as well as the measurement model used in cross-national epidemiological studies. Schwartz' cultural values provide a meaningful taxonomy to describe 'culture' and to examine how culture affects both the aetiology and phenomenology of CMDs. Objective: The present study examines to what extent Schwartz' cultural values correlate with prevalence rates of CMDs at the country-level. Method: Twenty-five countries were included in this study. Countries were included if data on cultural values and lifetime prevalence rates, from either the World Mental Health Surveys or the Global Burden of Disease Study, were available for at least one CMD. Spearman rank correlations were calculated between prevalence rates and cultural values, controlling for gross national income (GNI) per capita. Results: Affective disorders correlated with cultural values, after controlling for GNI. For anxiety disorders, correlations were lower but still offered meaningful insights. Correlations followed the circular structure of values, meaning that the strength of relationship decreased and increased again when moving around the circle: the strongest positive correlations were found with egalitarianism, and the strongest negative correlations with hierarchy and mastery. The autonomy-embeddedness dimension correlated weakly with the prevalence of CMDs. Conclusions: Diverging prevalence rates between high-income countries and low- and middle-income countries are associated with differences in cultural values. Values might not only relate to the aetiology of mental disorders, but most possibly affect the way in which psychological distress is expressed. As an example, in societies with a strong focus on embeddedness, the fear of stigma might be more pronounced. Cultural values offer a middle ground between culturally specific (i.e., emic) and universalist (i.e., etic) research. Highlights: Cultural values correlated with lifetime prevalence of common mental disorders. Egalitarianism was associated with higher prevalence rates, controlling for GNI. Hierarchy and mastery were associated with lower prevalence rates. Embeddedness and autonomy showed weak correlations with prevalence rates. Cultural values shape both the aetiology and phenomenology of mental disorders.